Microalgae Lipid Characterization - Yao, Linxing (2015)
To meet the growing interest of utilizing microalgae biomass in the production of biofuels and nutraceutical and pharmaceutical lipids, we need suitable analytical methods and a comprehensive database for their lipid components. The objective of the present work was to demonstrate methodology and provide data on fatty acid composition, lipid class content and composition, characteristics of the unsaponifiables, and type of chlorophylls of five microalgae. Microalgae lipids were fractionated into TAG, FFA, and polar lipids using TLC, and the composition of fatty acids in total lipids and in each lipid class, hydrocarbons, and sterols were determined by GC-MS. Glyco- and phospholipids were profiled by LC/ESI-MS. Chlorophylls and their related metabolites were qualified by LC/APCI-MS. The melting and crystallization profiles of microalgae total lipids and their esters were analyzed by DSC to evaluate their potential biofuel applications. Significant differences and complexities of lipid composition among the algae tested were observed. The compositional information is valuable for strain selection, downstream biomass fractionation, and utilization.